What Is the Association Among Epiphyseal Rotation, Translation, and the Morphology of the Epiphysis and Metaphysis in Slipped Capital Femoral Epiphysis?. Issue 5 (May 2021) - Novais, Eduardo N.; Hosseinzadeh, Shayan; Emami, Seyed Alireza; Maranho, Daniel A.; Kim, Young-Jo; Kiapour, Ata M.
Abstract: Background: Contemporary studies have described the rotational mechanism in patients with slipped capital femoral epiphysis (SCFE). However, there have been limited patient imaging data and information to quantify the rotation. Determining whether the epiphysis is rotated or translated and measuring the epiphyseal displacement in all planes may facilitate planning for surgical reorientation of the epiphysis. Questions/purposes: (1) How does epiphyseal rotation and translation differ among mild, moderate, and severe SCFE? (2) Is there a correlation between epiphyseal rotation and posterior or inferior translation in hips with SCFE? (3) Does epiphyseal rotation correlate with the size of the epiphyseal tubercle or the metaphyseal fossa or with epiphyseal cupping? Methods: We identified 51 patients (55% boys [28 of 51]; mean age 13 ± 2 years) with stable SCFE who underwent preoperative CT of the pelvis before definitive treatment. Stable SCFE was selected because unstable SCFE would not allow for accurate assessment of rotation given the complete displacement of the femoral head in relation to the neck. The epiphysis and metaphysis were segmented and reconstructed in three-dimensions (3-D) for analysis in this retrospective study. One observer (a second-year orthopaedic resident) performed the image segmentation and measurements of epiphyseal rotation and translation relative to the metaphysis, epiphyseal tubercle, metaphyseal fossa, and the epiphysis extension onto the metaphysis defined as epiphyseal cupping. To assess the reliability of the measurements, a randomly selected subset of 15 hips was remeasured by the primary examiner and by the two experienced examiners independently. We used ANOVA to calculate the intraclass and interclass correlation coefficients (ICCs) for intraobserver and interobserver reliability of rotational and translational measurements. The ICC values for rotation were 0.91 (intraobserver) and 0.87 (interobserver) and the ICC values for translation were 0.92 (intraobserver) and 0.87 (intraobserver). After adjusting for age and sex, we compared the degree of rotation and translation among mild, moderate, and severe SCFE. Pearson correlation analysis was used to assess the associations between rotation and translation and between rotation and tubercle, fossa, and cupping measurements. Results: Hips with severe SCFE had greater epiphyseal rotation than hips with mild SCFE (adjusted mean difference 21° [95% CI 11° to 31°]; p < 0.001) and hips with moderate SCFE (adjusted mean difference 13° [95% CI 3° to 23°]; p = 0.007). Epiphyseal rotation was positively correlated with posterior translation (r = 0.33 [95% CI 0.06 to 0.55]; p = 0.02) but not with inferior translation (r = 0.16 [95% CI -0.12 to 0.41]; p = 0.27). There was a positive correlation between rotation and metaphyseal fossa depth (r = 0.35 [95% CI 0.08 to 0.57]; p = 0.01), width (r = 0.41 [95% CI 0.15 to 0.61]; p = 0.003), and length (r = 0.56 [95% CI 0.38 to 0.75]; p < 0.001). Conclusion: This study supports a rotational mechanism for the pathogenesis of SCFE. Increased rotation is associated with more severe slips, posterior epiphyseal translation, and enlargement of the metaphyseal fossa. The rotational nature of the deformity, with the center of rotation at the epiphyseal tubercle, should be considered when planning in situ fixation and realignment surgery. Avoiding placing a screw through the epiphyseal tubercle—the pivot point of rotation— may increase the stability of the epiphysis. The realignment of the epiphysis through rotation rather than simple translation is recommended during the open subcapital realignment procedure. Enlargement of the metaphyseal fossa disrupts the interlocking mechanism with the tubercle and increases epiphyseal instability. Even in the setting of a stable SCFE, an increased fossa enlargement may indicate using two screws instead of one screw, given the severity of epiphyseal rotation and the risk of instability. Further biomechanical studies should investigate the number and position of in situ fixation screws in relation to the epiphyseal tubercle and metaphyseal fossa. Level of Evidence: Level III, prognostic study.